2016
DOI: 10.1039/c6tc02482c
|View full text |Cite
|
Sign up to set email alerts
|

Light-directed alignment, surface morphing and related processes: recent trends

Abstract: The immense potential of light responsive polymer materials toward technological applications in photonics, mechanics and micro-fabrication has been attracting increasing attention from both materials chemists and physicists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 149 publications
1
66
0
Order By: Relevance
“…The photon dose for the completion of migration [6,7,[9][10][11][12] becomes approximately 10 3 -fold lower than that for widely reported amorphous polymers [1][2][3] and amorphous molecular materials [13,14]. This can be ascribed to the occurrence of isothermal liquid crystal (LC) to isotropic phase transition in the process of trans-to-cis photoisomerization [6,7,11,[15][16][17]. The film material starts to move from the trans-rich regions to cis-rich ones, which is possibly initiated by the disparities of the viscosity and sharp gradient of surface tension at the boundary regions [6,7,11,15].…”
Section: Introductionmentioning
confidence: 89%
“…The photon dose for the completion of migration [6,7,[9][10][11][12] becomes approximately 10 3 -fold lower than that for widely reported amorphous polymers [1][2][3] and amorphous molecular materials [13,14]. This can be ascribed to the occurrence of isothermal liquid crystal (LC) to isotropic phase transition in the process of trans-to-cis photoisomerization [6,7,11,[15][16][17]. The film material starts to move from the trans-rich regions to cis-rich ones, which is possibly initiated by the disparities of the viscosity and sharp gradient of surface tension at the boundary regions [6,7,11,15].…”
Section: Introductionmentioning
confidence: 89%
“…The rod‐like trans Azs are isomerized most effectively when their transition moments are oriented parallel to the electric vector ( E ) of light. In the case of normally incident LPL, this leads to a statistical buildup of Az moieties oriented orthogonal to E , and the concurrent in‐plane alignment of BCP nanostructures . It was shown that the in‐plane alignment of cylinders proceeds through subdomain rotation in a cooperative and synchronized manner .…”
Section: Introductionmentioning
confidence: 99%
“…Photochromic liquid‐crystalline (LC) polymers represent a promising type of smart materials with high potential for a large variety of applications in optics and optoelectronics . Among different types of photochromic fragments incorporated in polymer matrices, the azobenzene moieties are the most remarkable chromophores capable of reversible E – Z isomerizing.…”
Section: Introductionmentioning
confidence: 99%
“…Among different types of photochromic fragments incorporated in polymer matrices, the azobenzene moieties are the most remarkable chromophores capable of reversible E – Z isomerizing. Several unique advantages of the azobenzene molecules make them the most popular photochrome, such as high quantum yield of photoisomerization, high fatigue resistance, and extreme change in the shape as well as in dipole moment during isomerization . Photoisomerization of azobenzene fragments in LC media enables to realize isothermal phase transitions .…”
Section: Introductionmentioning
confidence: 99%